2010
DOI: 10.5171/2010.694811
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Approach to Inter-organizational System Implementation and Evaluation: the Case of Government-to-Business

Abstract: Over the years, government-to-business (G2B) as an inter-organizational system has emerged as an essential part of e-government systems. Its development and usage have not only been expected to contribute to efficient and effective operations, but G2B is also anticipated for better transparency, reduced costs and improved process. However, although a rich body of literature exists regarding G2B, there is a lack of empirical research finding in understanding the system from multiple stakeholders' perspectives. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Self-service applications 24 (Alghamdi & Beloff, 2016;Alomar & de Visscher, 2017;Hung et al, 2012;Jansen et al, 2010;Kindel et al, 2014;Lee et al, 2011;Mbeche et al, 2017;Nguyen et al, 2020;Pinem et al, 2018;Rammea & Grobbelaar, 2017;Reddick & Roy, 2013;Riyadh et al, 2019;Santa et al, 2019;Seo et al, 2018;Shao et al, 2015;Soong et al, 2020;Thi et al, 2014;Tung & Rieck, 2005;Ulman et al, 2012;van den Boer et al, 2012van den Boer et al, , 2016van den Boer et al, , 2017van den Boer et al, , 2014Vejačka, 2018) Interorganizational systems 14 (Arendsen et al, 2008(Arendsen et al, , 2014(Arendsen et al, , 2006Bharosa et al, 2018;Gunasekaran et al, 2009;Haag et al, 2013;Kassim & Hussin, 2010;Lian, 2015;Mohd Nawi et al, 2016;Naggi & Agostini, 2011;Olaleye & Sanusi, 2017;Sambasivan et al, 2010;Urciuoli et al, 2013) In terms of research philosophy, most papers were found to be following a positivist research philosophy and a deductive approach towards theory development. Regarding methodological choice, 30 papers reported research relying on one quantitative method, 2 papers on quantitative and qualitative methods, and 4 papers on qualitative m...…”
Section: # Of Papers Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-service applications 24 (Alghamdi & Beloff, 2016;Alomar & de Visscher, 2017;Hung et al, 2012;Jansen et al, 2010;Kindel et al, 2014;Lee et al, 2011;Mbeche et al, 2017;Nguyen et al, 2020;Pinem et al, 2018;Rammea & Grobbelaar, 2017;Reddick & Roy, 2013;Riyadh et al, 2019;Santa et al, 2019;Seo et al, 2018;Shao et al, 2015;Soong et al, 2020;Thi et al, 2014;Tung & Rieck, 2005;Ulman et al, 2012;van den Boer et al, 2012van den Boer et al, , 2016van den Boer et al, , 2017van den Boer et al, , 2014Vejačka, 2018) Interorganizational systems 14 (Arendsen et al, 2008(Arendsen et al, , 2014(Arendsen et al, , 2006Bharosa et al, 2018;Gunasekaran et al, 2009;Haag et al, 2013;Kassim & Hussin, 2010;Lian, 2015;Mohd Nawi et al, 2016;Naggi & Agostini, 2011;Olaleye & Sanusi, 2017;Sambasivan et al, 2010;Urciuoli et al, 2013) In terms of research philosophy, most papers were found to be following a positivist research philosophy and a deductive approach towards theory development. Regarding methodological choice, 30 papers reported research relying on one quantitative method, 2 papers on quantitative and qualitative methods, and 4 papers on qualitative m...…”
Section: # Of Papers Papersmentioning
confidence: 99%
“…Monomethod -Qualitative 4 (Kassim & Hussin, 2010;Mohd Nawi et al, 2016;Naggi & Agostini, 2011;Rammea & Grobbelaar, 2017) Table 8 presents the time horizon of the research and the strategy among the papers. Survey (30 papers), vignette studies (3 papers), and case study (5 papers) were the three strategies identified, meaning, almost all studies are cross-sectional in nature, but one conducted survey at three different moments in time.…”
Section: Positivist Deductivementioning
confidence: 99%
See 1 more Smart Citation
“…One form of institutional pressures is the normative pressure, for instance supplier expectation. As the government e-procurement system in an interorganizational system, it requires participation from both the federal government agencies as buyers and businesses organizations as suppliers (Kassim & Hussin, 2010b). With this regard, having to confirm to suppliers expectations that government agencies use electronic system in their procurement process and management is found to be a significant determinant for the system use (Dooley & Purchase, 2006;Leipold et al, 2004).…”
Section: Supplier Expectation and Public E-procurement System Usementioning
confidence: 99%